Innovative teaching strategies in nursing and related health professions - Bradshaw, Martha J.;Lowenstein., Arlene J. (Sudbury, Massachusetts : Jone and Bartlett Learning, 2011)
Offers how-to strategies for incorporating the burgeoning field of technology into the classroom. New topics include Web 2.0 technologies such as blogs and podcasts.
Section 1. Foundational approaches to teaching and learning -- section 2. Teaching in structured settings -- section 3. Simulation and imagination -- section 4. Educational use of technology -- section 5. Teaching in unstructured settings -- section 6. Evaluation.
Includes bibliographical references and index.
Keywords: NURSING -- STUDY AND TEACHING